2014
DOI: 10.1097/01.sa.0000450916.06503.48
|View full text |Cite
|
Sign up to set email alerts
|

Individually Optimized Hemodynamic Therapy Reduces Complications and Length of Stay in the Intensive Care Unit

Abstract: all are aware a study is being conducted. This problem arises in every nonblinded study in the ICU, especially when the team feels committed toward 1 approach (the more advanced one in this study). The only method to alleviate such bias would be to directly monitor the interventions, but I'm not certain that such an approach is feasible, and even if it were that it would resolve this bias completely. Despite these reservations, this is an excellent study that shows for the first time that the content of a prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…Our data show that both hemodynamic monitoring and therapy are clinically important in order to increase CI, since it has been shown that they reduce the length of the stay on intensive care units [12]. The effects of hemodynamic treatments are similar to other studies [13]; in other studies lower dosages of catecholamines were applied [14,15]; targeted MAP levels were accomplished to 92% of monitoring time.…”
Section: Discussionsupporting
confidence: 81%
“…Our data show that both hemodynamic monitoring and therapy are clinically important in order to increase CI, since it has been shown that they reduce the length of the stay on intensive care units [12]. The effects of hemodynamic treatments are similar to other studies [13]; in other studies lower dosages of catecholamines were applied [14,15]; targeted MAP levels were accomplished to 92% of monitoring time.…”
Section: Discussionsupporting
confidence: 81%
“…A more recent GDT trial in patients undergoing cardiac surgery showed a reduction in length of stay and complications in the group with fluids management that was guided by stroke volume variation (173). Although this study was not powered to detect changes in the incidence of AKI, there was a trend toward reduced AKI in the protocol group (three versus eight; P=0.20).…”
Section: Prevention Of Aki Nonpharmacologic Strategiesmentioning
confidence: 54%
“…This type of personalized therapy based on a step-by-step analysis of the determinants of organ perfusion has been shown to reduce length of stay in selective populations with CS. 79 In other types of shock, rapid hemodynamic stabilization based on oxygenation targets or lactate clearance has also increased survival. 29,80 However, there is no clinical evidence showing the superiority of a flowdirected approach relative to a pressure-based strategy.…”
Section: Maximum Vasoconstrictionmentioning
confidence: 99%